(3eHGOF GdHMK GdYdej (B:s (3GdefWdbGJ GdfXQjI h GdJhLgGJ GdJWHjbjI (B/s - (3JeGQ, jhSas ((3GdLRGFQ (B:s (3OGQ eOfj ,s, 2021)
(3jMGhd GdcJGH JbOje GdeHGOF GdGGSjI ddHMK GdYdej h Ydi hLg GdJMOjO Jdc GdNGUI jYde GdGYdGe h GdGJUGd chfg dG jRGd jYGfj ef GUGdI GdefGgL h GdGOhGJ GdJMdjdjI h GYJeGOg Ydi eG GfJLg GdYdhe GdeYQajI GdGNQi Ydi TGcdg dYdhe GdSjGSjI Yde GdGLJeGY h Yde GdGMUGA h ZjQgG h gPG eQOg Gdi Gf Yde GdGYdGe h GdGJUGd jOQS GdaQO aj YdGbGJg HhSGFd GdGYdGe ef LgI h GdGKGQ GdfGLeI deVGejf Jdc GdhSGFd Ydi GdeLJeY cHfj ceG jOQS ef LgI GNQi GdXGgQI GdGJUGdjI GdJj bGd YfgG GHhJh Gjch (Bumberto eco (3Gf eLGdGJgG (B-(3GdGJUGd(B- (3JcGO Jchf dG eJfGgjIs
(3HjHdjhZQGajG(B:(3U(B.219-233 (3edGMXI (B: 212-218s
Keywords: (3GdHMK GdYdejs; (3eHGOF GdHMK GdYdejs